2004
DOI: 10.1007/s00704-004-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the land surface on the transition from dry to wet season in Amazonia

Abstract: SummaryAnalysis of the fifteen years of European Centre for Medium Range Weather Forecasts (ECMWF) reanalysis suggests that the transition from dry to wet season in Southern Amazonia is initially driven by increases of surface latent heat flux. These fluxes rapidly reduce Convective Inhibition Energy (CINE) and increase Convective Available Potential Energy (CAPE), consequently providing favourable conditions for increased rainfall even before the large-scale circulation has changed. The increase of rainfall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 30 publications
10
94
0
1
Order By: Relevance
“…Previous studies suggest that CAPE, CIN and zonal/meridional winds (Fig. 2c, e and f) from radiosondes may also illustrate large-scale thermodynamical changes and moisture transport associated with wet, dry and transitional periods (e.g., Li and Fu, 2004;Fu and Li, 2004). Radiosonde daily maximum values indicate only small seasonal changes in CAPE and CIN, although we observe that the transitional periods between the dry and wet seasons promote maximum relative CAPE trends coupled with relatively lower CIN and heightened moisture.…”
Section: Radiosonde Surface Meteorology and Large-scale Forcing Datamentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies suggest that CAPE, CIN and zonal/meridional winds (Fig. 2c, e and f) from radiosondes may also illustrate large-scale thermodynamical changes and moisture transport associated with wet, dry and transitional periods (e.g., Li and Fu, 2004;Fu and Li, 2004). Radiosonde daily maximum values indicate only small seasonal changes in CAPE and CIN, although we observe that the transitional periods between the dry and wet seasons promote maximum relative CAPE trends coupled with relatively lower CIN and heightened moisture.…”
Section: Radiosonde Surface Meteorology and Large-scale Forcing Datamentioning
confidence: 83%
“…The Amazon forest is the largest tropical rain forest on the planet, featuring prolific and diverse cloud conditions that span "wet" and "dry" precipitation regimes. These regimes and associated variations in cloud types, coverage and intensity from sub-daily to seasonal scales, are interconnected to large-scale shifts in the thermodynamic forcing and coupled local cloudscale feedbacks (e.g., Fu et al, 1999;Machado et al, 2004;Li and Fu, 2004;Fu and Li, 2004;Misra, 2008). The inability of GCMs to adequately represent clouds over such a complex and expansive tropical area sets apart GoAmazon2014/5 as an important asset for the improvement of GCM cloud parameterizations and simulations of possible climate change (e.g., Williams et al, 2002;Richter and Xie, 2008;Nobre et al, 2009;Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although, a further analysis will be done in future works in order to identify the causes of the model deficiencies, particularly the biases observed over the Amazon, northern and eastern Brazil in temperature and precipitation. Many studies have linked delayed onset of the rainy season in the Amazon to soil moisture (e.g., Fu et al 1999;Fu and Li 2004;Li and Fu 2004). Nevertheless, the processes related with model biases over eastern Brazil and the SACZ regions are not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this lengthening are still not very clear. It has been suggested that large-scale influence of SST gradients of the North and South Atlantic (49,54,55), or a strong influence of dry season ET (56,57), in response to a seasonal increase of solar radiation (58), may play a role.…”
Section: Significancementioning
confidence: 99%